Real-time video enhances skill development in junior alpine skiers during a single week of summer camp training - Bacharach, D. W. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Using a delayed video system in alpine ski race training over the course of 10 weeks (1) as well as one week (2) has been shown to have good correlations (r=.84-.93) to skill acquisition in skiers age 9-17 years of age. What remains unknown is what type of information skiers of different ages and sex glean from reviewing video and how on-hill video might change their focus of attention during training. Therefore, the purpose of this study was to determine how real-time delayed video feedback impacts various elements of ski skills during three days of SL training and three days of GS training by junior alpine ski racers.